Short history of the autopsy: Part II From the second half of the 16th century to contemporary times - Gulczyński, Jacek; Iżycka-Świeszewska, Ewa; Grzybiak, Marek (Polish Journal of Pathology, 2010)
We present the second part of our review concerning the history of autopsy. During the development of medicine the role of autopsy was obviously changing. Concurrently with the progress in the anatomical knowledge, the anatomists observed and noted both single anomalies and repetitive changes which correlated with symptoms in living patients. This is how anatomopathology came into being. We present the most famous people engaged in autopsy comprehension. We discuss main trends and ideas influencing the phenomenon of autopsy in the analyzed period: from sporadic public dissections, through theatra anatomica, introduction of autopsy to the hospital medicine and separation of anatomopathology as a medical speciality. The golden age of autopsy was the 19th century and the first half of the 20th century, with a consecutive decline in frequency. Nevertheless, despite the progress in diagnostics in vivo , it seems that autopsy will keep its important place in medicine according to the old motto “Mortui vivos docent” (the dead teach the living).